Pernyataan Apologetik dan Misi Paulus: Memahami Motif Paulus menulis Surat Roma - Fredy Fredy (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
Paul had a specific motive for writing to the church in Rome. This motive is often misunderstood, and the letter to the Romans is viewed merely as a lengthy and comprehensive theological exposition. This paper aims to elucidate Paul’s motive based on Romans 15:22–33, which reveals the purpose behind his writing. This study employs a qualitative method using a Textual Exegesis approach supported by Rhetorical Analysis (specifically deliberative/persuasive rhetoric). The research focuses on reinterpreting Paul’s motive for writing the letter to the Romans. It examines two dimensions—apologetics and mission—which are not commonly combined in a single text. A sequential analysis of the motives behind the writing of the Letter to the Romans was found: to explain Paul’s hope of making Rome a base for his mission; to refute the charge of antinomianism against him by directing aid to Jerusalem; and to involve the Roman church in the mission by asking them to pray for key matters.